Sustentabilidade e economia nos meios da construção civil - COIMBRA, Andrielli Silva; DIAS, Gabriela Correia Guimarães; PEREIRA, Luiz Eduardo Barbosa; CIPRIANO, Paulo Henrique dos Santos (240, 2023)
A integração da sustentabilidade na construção civil visa equilibrar práticas ambientalmente responsáveis com benefícios econômicos. Isso é alcançado através da promoção da eficiência energética, utilização de materiais sustentáveis, gestão eficaz de resíduos, certificações ambientais, adoção de tecnologias inovadoras, planejamento urbano sustentável, reuso de água e investimento em treinamento. Essa abordagem não apenas reduz os impactos ambientais, mas também resulta em economias a longo prazo, eficiência operacional e valorização de propriedades. A integração efetiva de práticas sustentáveis na construção civil não apenas beneficia o meio ambiente, mas também pode resultar em vantagens econômicas significativas a curto e longo prazo, promovendo uma abordagem mais equilibrada e responsável para o setor.

The integration of sustainability in construction aims to balance environmentally responsible practices with economic benefits. This is achieved through the promotion of energy efficiency, use of sustainable materials, effective waste management, environmental certifications, adoption of innovative technologies, sustainable urban planning, water reuse and investment in training. This approach not only reduces environmental impacts, but also results in long-term savings, operational efficiencies and property appreciation. The effective integration of sustainable practices in construction not only benefits the environment, but can also result in significant economic advantages in the short and long term, promoting a more balanced and responsible approach to the sector. The integration of sustainability in construction aims to balance environmentally responsible practices with economic benefits. This is achieved through the promotion of energy efficiency, use of sustainable materials, effective waste management, environmental certifications, adoption of innovative technologies, sustainable urban planning, water reuse and investment in training. This approach not only reduces environmental impacts, but also results in long-term savings, operational efficiencies and property appreciation. The effective integration of sustainable practices in construction not only benefits the environment, but can also result in significant economic advantages in the short and long term, promoting a more balanced and responsible approach to the sector.
sustainability and economy in civil construction
Keywords: Sustentabilidade; Economia; Construção civil; Gestão e Negócios